Upregulation of Tumor Necrosis Factor-α-Induced Protein 8-Like 2 mRNA Is Negatively Correlated with Serum Concentrations of Tumor Necrosis Factor-α and Interleukin 6 in Type 2 Diabetes Mellitus - Yongliang Liu; Xinmei Wang; Yan Zhao; Peiqing Zhao; Lianqing Wang; Qiaoli Zhai; Xiaowei Zhang; Wenxiu Tian; Xinxin Xiang; Tao Li (Journal of Diabetes Research)
Background. Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2 or TNFAIP8L2) is a negative regulator of natural and adaptive immunity. The role of TIPE2 in type 2 diabetes mellitus (T2DM) remains unknown, although TIPE2 plays key roles in preserving inflammatory homeostasis. Methods. TIPE2 expression was measured by Western blotting and real-time polymerase chain reaction (RT-PCR) in peripheral blood mononuclear cells (PBMCs) isolated from T2DM patients and healthy controls, and tumor necrosis factor-α (TNF-α), high-sensitivity C-reactive protein (hsCRP), interleukin 6 (IL-6), and other related biometabolic parameters were detected using a nephelometer or by ELISA. Differentiated THP-1 cells were exposed to siTIPE2 and TIPE2 adenovirus. Results. TIPE2 was significantly increased in PBMCs from T2DM patients compared with those from healthy controls and was negatively correlated with serum TNF-α, IL-6, and hsCRP concentrations but positively correlated with HbA1c and LDL-C in T2DM patients. High glucose treatment (50 mmol/L) can upregulate the expression of TIPE2 and cytokine secretion in differentiated THP-1 cells. siTIPE2 infection exacerbated the increased TNF-α and IL-6 concentrations in differentiated THP-1 cells under high glucose conditions (50 mmol/L), while infection with TIPE2 adenovirus reversed the increased TNF-α concentration. Conclusions. The present study indicates that TIPE2 may participate in T2DM by regulating TNF-α production.